How can we address the surge of low-quality systematic reviews and their impact on high journal rejection rates? (Colombia Medica, 2024)
Journals have experienced a significant rise in submissions of systematic reviews and other types of reviews that often fall short of acceptable quality standards. These shortcomings typically stem from insufficient rigor in their methodology, reporting, or critical appraisal. As a result, these submissions are frequently rejected raising concerns about the standards authors are following when preparing such work. This growing trend of low-quality reviews not only places a burden on editorial teams but also poses a risk to the scientific community by potentially disseminating flawed or unreliable conclusions. Ensuring that articles maintain high standards is crucial for preserving the integrity of the scientific literature and facilitating evidence-based decision-making. In an effort to address this problem, this viewpoint editorial aims to offer concepts and recommendations on available tools for future authors to improve the quality of their reviews, as well as to guide readers and potential journal reviewers on how to critically interpret these articles.